A sister's hope [large type] - Brunstetter, Wanda E. (Brunstetter, Wanda E. Sisters of Holmes County, 2010)
Martha is the youngest of the Hostettler sisters and the most daring. While her main focus has been on her dog breeding business Martha has also been troubled about the continuing attacks against her family and home in an Ohio Amish community. When the prime suspect turns out to be Luke Friesen - the man she loves - Martha decides to play detective. Will her hope in Luke's innocence be enough to bring the real criminal to justice?